2016
DOI: 10.1093/icesjms/fsw016
|View full text |Cite
|
Sign up to set email alerts
|

Size matters: fishing less and yielding more in smaller-scale fisheries

Abstract: Several factors influence catches and the sustainability of fisheries, and such factors might be different depending on the scale on which fisheries work. We investigated the existence of possible subdivisions within small-scale fisheries (SSF) themselves, regarding their economic performance and relative social and environmental impacts to understand which categories of these two types of fleets are best positioned to support sustainability. By doing so, we investigated if it is a good strategy for SSF to aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Data for 2011 and 2014 were provided by Petrobras, a Brazilian oil company, for nine municipalities on the northern coast of the state, as part of a monitoring program in regions subject to possible impacts of offshore oil platforms (Damásio et al, 2020). One municipality on the eastern coast of the state (Baía Formosa) was sampled by the research team between 2013 and 2014 (Damasio et al, 2016). Thus, data from these different sources were combined and proportionality of landings for different municipalities as well as linear interpolation were used for missing data.…”
Section: Detailed Reconstruction Process For Each Statementioning
confidence: 99%
“…Data for 2011 and 2014 were provided by Petrobras, a Brazilian oil company, for nine municipalities on the northern coast of the state, as part of a monitoring program in regions subject to possible impacts of offshore oil platforms (Damásio et al, 2020). One municipality on the eastern coast of the state (Baía Formosa) was sampled by the research team between 2013 and 2014 (Damasio et al, 2016). Thus, data from these different sources were combined and proportionality of landings for different municipalities as well as linear interpolation were used for missing data.…”
Section: Detailed Reconstruction Process For Each Statementioning
confidence: 99%
“…Over the years, many attributes essential for defining and valuing SSF have been proposed, including the size and type of boat, engine horse power, equipment type, time commitment, catch rates and disposal, environmental knowledge, significance of fishing as a livelihood, and marginality, among others (Kurien, 1996;Berkes, 2001;Kittinger, 2013). Some lists emphasize the importance of technological aspects of SSF (Pitcher et al, 1998), while others address combinations of technological, environmental, social, and political parameters to explore finer variations within SSF and between these two, taken-for-granted categories (Johnson, 2006;De Melo Alves Damasio et al, 2016). Several in depth studies grapple with the specifics and limits of national fisheries definitions, including in India (Jadhav, 2018b), Brazil (De Melo Alves Damasio et al, 2016, Peru (Fréon et al, 2014), Azores islands (Carvalho et al, 2011), and Canada (Gibson and Sumaila, 2017), while others address regional challenges such as in the EU (García-Flórez et al, 2014;Natale et al, 2015;Davies et al, 2018).…”
Section: Debating the Definition Of Small-scale Fisheriesmentioning
confidence: 99%
“…A future expansion in Icelandic small-scale fisheries is a possibility, with arguments in the academic literature for the increased use of these smaller vessels compared to traditional trawling methods, due to perceived advantages in terms of the quality of the product, timely landing process, much lower upfront investment costs, and efficient delivery to major markets [19]. Chambers et al [15] found evidence that small-scale fisheries contribute incalculably to cultural identity, sense of place and pride, physical and emotional wellbeing, and food security.…”
Section: Constraining Factors and Concernsmentioning
confidence: 99%